Nutritional Deficiencies in Morbid Obese Patients Before and After Laparoscopic Sleeve Gastrectomy - Şen, Ozan; Çetin, Dilara; Dumanlı, Göknel; Türkçapar, Ahmet Gökhan (Turkish Journal of Gastroenterology, 2022)
Background: This study aims to assess the prevalence of preoperative and postoperative nutritional deficiencies and associated factors in patients who are eligible for laparoscopic sleeve gastrectomy. Methods: Patients who underwent primary laparoscopic sleeve gastrectomy between December 2018 and April 2020 were included in the study. All patients were screened by detailed laboratory tests pre- and post-laparoscopic sleeve gastrectomy 6th and 12th months. Patients’ data, which were recorded prospectively, were analyzed retrospectively. Results: A total of 228 patients were included in the study. The mean age was 39 ± 11.5 (60% female), and the mean body mass index was 41.2 ± 6.3 kg/m2. In the preoperative period, anemia was detected in 20 female patients (9%), low ferritin levels were detected in 25%, B12 and folic acid deficiencies were detected in 2.6% and 12.3%, respectively, and vitamin D deficiency was detected in 76% of the patients. During the postoperative follow-up, 77% of the patients received multivitamin supplements regularly. Mean body mass index regressed to 27.1 ± 4.2 kg/m2 in the first year. Incidence of anemia was found at 4.8%, low ferritin levels were 14%, folate deficiency was 5.3%, B12 deficiency was 5.3%, and vitamin D deficiency was 25% in the 12th month. Vitamin A, zinc, biotin, and thiamine deficiencies were 8.8%, 6.6%, 11%, and 2.2% in the 12th month, respectively. Conclusion: In the preoperative period, we detected significant deficiencies in some vitamins. The incidence of de novo vitamin deficiency during post-laparoscopic sleeve gastrectomy follow-up was low. Regular multivitamin–multimineral use may have an effect on this Cite this article as: Şen O, Çetin D, Dumanlı G, Türkçapar AG. Nutritional deficiencies in morbid obese patients before and after laparoscopic sleeve gastrectomy. Turk J Gastroenterol. 2022;33(10):885-890.